Enabling PZT bimorph actuator with passive polysilicon structure. Issue 20 (11th September 2017) - Chen, S.‐H.; Michael, A.; Kwok, C. Y.
Abstract : For the first time, a bimorph thin film lead zirconate titanate (PZT) micro‐actuator with thick polysilicon as a passive structural layer is reported. A simple micro‐cantilever actuator consisting of 1000 µm long and 250 µm wide with 4 µm thick polysilicon structure flanked by a piezoelectric active layer on the top and bottom side has been fabricated to demonstrate such novel bimorph configuration. The actuator displays a flat profile with only 2 µm of tip deflection which indicates a balanced stress distribution in the structure. It is driven alternatively in both directions, demonstrating its unique suitability for micro‐actuation mechanisms where a passive structural layer is required to enhance the mechanical performance and reliability of the system. The static and dynamic measurements show similar characteristics for the top and bottom actuation. The actuator has a measured resonance frequency of 6.3 kHz, and displacement voltage sensitivities of 17.9 and 25.6 nm/V in the upward and downward direction, respectively.